GAMBARAN PELAKSANAAN PEMBERIAN ASI EKSKLUSIF PADA BAYI 6-12 BULAN DI WILAYAH KERJA PUSKESMAS TALANG LEAK KABUPATEN LEBONG TAHUN 2017 - Wijayanti, Venti Kusuma (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
Based on the data from the Provincial Health Office Bengkulu the highest percentage of exclusive breastfeeding in Lebong area of 2.573 (74%), and the lowest was in Bengkulu City by 1.376 (38%). InLebong, the highest rank of exclusive breastfeeding health center is in MuaraAman (23.7%), whereas the lowest Exclusive Breastfeeding coverage was in Talang Leak Health Center which was only 40 babies (54%). The goal to be achieved is the implementation of Exclusive Breastfeeding in infants aged 6-12 months in the working area of Talang Leak Health Center in LebongDistrict in 2017.The research method used was descriptive, using Total Sampling technique, the research was conducted in the Working Area of Talang Leak Health Center of Lebong District, the overall sampling of mothers with babies aged 6-12 months who breastfed amounted to 40 babies.The results showed that from 40 respondents, almost half of infants (22.5%) were not exclusively breastfed. And almost all infants (77.5%) were Exclusive breastfed.Conclusions and suggestions, almost half of infants who are not exclusive breastfed because the mother still provides additional foods such as water / mineral water, some give honey as a tradition of local custom. Almost all of the purified exclusive breastfeeding without any given to infants of 40 respondents. Suggestion, to Dehasen Bengkulu Midwifery Academy hopefully this research can be used as a reference material and additional reading in library, for Talang Leak health center it can be an input and information material for officer in giving counseling about exclusive breastfeeding on infant 6-12 months, for the researcher, as benchmark to apply the implementation of exclusive breastfeeding in infants 6-12 months.